2017
DOI: 10.1186/s12245-017-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Human and equipment resources for difficult airway management, airway education programs, and capnometry use in Japanese emergency departments: a nationwide cross-sectional study

Abstract: BackgroundAlthough human and equipment resources, proper training, and the verification of endotracheal intubation are vital elements of difficult airway management (DAM), their availability in Japanese emergency departments (EDs) has not been determined. How ED type and patient volume affect DAM preparation is also unclear. We conducted the present survey to address this knowledge gaps.MethodsThis nationwide cross-sectional study was conducted from April to September 2016. All EDs received a mailed questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(61 reference statements)
1
11
0
1
Order By: Relevance
“…A nationwide survey on emergency airway management in Japan found that a quantitative capnometry is available to confirm endotracheal tube placement. Interestingly, the same study showed only 47.8% of the EDs routinely use capnometry for this purpose . This might indicate that the lack of familiarity with a capnometry device, not availability, is the main reason of not using capnometry in airway management and in PSA, as shown in our study.…”
Section: Discussionsupporting
confidence: 48%
“…A nationwide survey on emergency airway management in Japan found that a quantitative capnometry is available to confirm endotracheal tube placement. Interestingly, the same study showed only 47.8% of the EDs routinely use capnometry for this purpose . This might indicate that the lack of familiarity with a capnometry device, not availability, is the main reason of not using capnometry in airway management and in PSA, as shown in our study.…”
Section: Discussionsupporting
confidence: 48%
“…We believe that, in collaborative efforts between research teams that are adept at generating high‐quality science, such investigations will provide emergency physicians with important opportunities for improving the quality and safety of airway management practice. For researchers and professional organizations, the gained knowledge will not only advance research into the determination of optimal airway management strategies but also facilitate the development of high‐quality clinical guidelines as well as their dissemination to the EDs nationally, which will, in turn, improve the outcomes of critically ill and injured patients in the ED.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Importantly, to reap the benefits of a well-designed DAT, it is crucial that those who use the DAT are knowledgeable about its organization and have acquired expertise on all included devices through clinical training and simulations. As a dedicated DAT is often present in sites providing general anesthesia, this is not consistently the case according to recent audits and surveys [6, 7]. Importantly, as most airway emergencies develop during the induction phase, incidents can occur throughout the anesthetic process, including extubation [8] and all the way to the postanesthesia care unit.…”
Section: Introductionmentioning
confidence: 99%